Constructing high-quality rest facilities to maximise performance and ensure patient safety. Issue 3 (23rd July 2021) - Silva, Geeth; Yam, Aiken; Court, Jessica; Imtiaz, Rabia; Chisholm, Cath
Abstract : Introduction: Junior doctors are working in an increasingly overstretched National Health Service. In 2018, Kettering General Hospital (KGH) was awarded £60 800 of government funds to create high-quality rest facilities and improve junior doctor well-being. Methods: An audit and survey in KGH identified the structural and functional improvements needed. From November 2019 to June 2020, £47 841.24 was spent on creating new rest facilities. On completion, a postaction review assessed how the changes impacted morale, well-being and quality of patient care. Results: The majority of doctors were happy with the new rest areas (60%), a majority felt that they would use the on-call room area (63%) and the renovation improved morale and well-being. There was an increased ability to take breaks. However, the majority of doctors are not exception-reporting missing breaks: 79% (2019), 74% (2020). Conclusions and Implications: This report recommends the maintenance of increased staffing levels and rest facilities during the recovery phase of COVID-19. The remaining £12 958.76 should be directed at sustaining the quality of KGH rest facilities. Lastly, the rate of exception-reporting must be increased through improving awareness, exploring alternative methods and supporting the action when necessary. The continual investment into rest facilities ensures workforce well-being and translates into patient safety.